Descontrole glicêmico do diabetes tipo 2 e fatores associados em um Hospital Universitário de Cuiabá - Mato Grosso - Almeida, Vitesinha Rosa dos Santos (2021)
Type 2 Diabetes is a metabolic disorder of multifactorial origin. It is considered as one of the most prevalent disorders among chronic non-communicable diseases today. Its representativeness is approximately 90% to 95% of all cases of diabetes and its prevalence increases with age. It is pointed out as a serious public health problem, harmfully impacts biopsychosocial and cultural aspects of life, as well as health systems worldwide. Brazil ranks fifth among countries with the highest number of adults with this disease. Objective: To analyze the prevalence of glycemic control of type 2 diabetes and to identify the associated factors. Methodology: This is a cross-sectional study, with secondary data obtained through a review of electronic medical records from a university hospital in Cuiabá-MT. The studied population consisted of 338 patients, over 18 years of age, diagnosed with type 2 diabetes and who were being monitored at the endocrinology outpatient clinic. The association between the elevation of glycated hemoglobin and sociodemographic factors, lifestyle and clinical conditions was investigated. In the bivariate analysis of the data, the chi-square test, crude prevalence ratios with their respective confidence intervals of 95% were used and in the multiple analysis, Poisson Regression model with robust variance without hierarchical blocks and considering hierarchical blocks. The variables that presented p<0.05 remained in the final models. Results: The results showed that 47.24% of the patients had altered glycated hemoglobin, with a mean age of 58.07 years and most of them were female (73.08%). It was observed higher prevalence of altered hemoglobin in female patients (48.18%), non-white (47.62%), with a partner (47.35%), with schooling without information (58.54%) origin of other municipalities (56, 79%). In the adjusted analysis by the Poisson multiple regression model with robust variance, the following factors remained associated with statistical significance to the outcome: fasting glycemia; the use of insulin; post prandial glycemia; the interaction between age group and time of diagnosis of diabetes; non-physical activity; origin; age group 59 years or younger; time of diagnosis of diabetes greater than 10 years and Systemic Arterial Hypertension. Considering the hierarchical blocks that remained associated with the alteration of glycated hemoglobin with statistical significance, the variables age group of 59 years or less; physical activity, the use of insulin and postprandial glycemia, altered fasting glucose. Conclusion: It was possible to identify a high prevalence of inadequate glycemic control in almost half of the diabetic population treated at the outpatient clinic. The higher levels of glycated hemoglobin were associated with several risk factors, such as younger individuals, those who did not perform physical activity, diagnosed more than 10 years ago, who used insulin, postprandial glucose tests, altered fasting glucose, hypertension and where patients were from, indicating that there are factors that should be considered, such as behavioral factors and if not weighted, tend to compromise good glycemic control.